2022
DOI: 10.31258/raje.5.2.81-90
|View full text |Cite
|
Sign up to set email alerts
|

Strategi dan kebijaksanaan P4GN dalam menciptakan penggiat anti Narkoba di lingkungan kerja

Abstract: Drug abuse in Indonesia has reached an alarming level. The largest proportion of drug abusers in 2017 was the group of private workers and laborers, which was 59%. BNNK Batam in collaboration with trade unions and academics conducted a workshop with the theme of strategies and policies on Prevention, Eradication, Abuse, and Illicit Trafficking of Narcotics (P4GN) in creating anti-drug activists in the work environment. The purpose of this workshop is so that the participants can become BNN activists in the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…This shows that the better the educational strategy perceived by consumers, the higher the level of consumer understanding in knowledge about drugs. Thus, the evidence of this study is in line with research conducted by (Jabar dkk., 2021;Mintawati & Budiman, 2021;Prasetyo, 2022), who said that the educational strategy had a positive and significant effect on the level of understanding. So it can be concluded that the second hypothesis (H2) is accepted.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that the better the educational strategy perceived by consumers, the higher the level of consumer understanding in knowledge about drugs. Thus, the evidence of this study is in line with research conducted by (Jabar dkk., 2021;Mintawati & Budiman, 2021;Prasetyo, 2022), who said that the educational strategy had a positive and significant effect on the level of understanding. So it can be concluded that the second hypothesis (H2) is accepted.…”
Section: Resultsmentioning
confidence: 99%
“…Remaja yang juga sering disebut sebagai golden age, merupakan masa transisi dari kanak-kanak ke dewasa, dimana selain peran keluarga, peran lingkungan pergaulan sangat penting dalam menggembleng mental dan psikologis mereka. Tidak sedikit para remaja yang kurang perhatian orang tua dan salah dalam pergaulan, berakibat buruk, salah satunya terjerumus dalam penyalahgunaan Narkoba (Prasetyo, 2022a) Masjid selain sebagai tempat untuk beribadah kepad Allah SWT, pada jaman Rasulullah juga digunakan untuk bermacam-macang kegiatan diantaranya untuk kegiatan pendidikan dan pengajaran, kegiatan pemberdayaan ekonomi umat, kegiatan peradilan, kegiatan pemerintahan dan sebagainya. Pada saat ini sudah sewajarnya Masjid tidak hanya digunakan sebagai tempat ibadah saja, melainkan dapat digunakan sebagai tempat untuk mengatasi segala permasalahan yang dihadapi oleh umat islam.…”
Section: Pendahuluanunclassified